On assessing trait rumination using the Ruminative Response Scale - Int-Veen, Isabell; Ehlis, Ann-Christine; Fallgatter, Andreas J.; Rosenbaum, David (Frontiers in Psychology, 2024)
Introduction This study explores the stability of scores on psychometrically validated trait questionnaires over time. We illustrate potential pitfalls through a larger study that used the Ruminative Response Scale (RRS) to categorize participants prior to study inclusion into two groups based on their habitual tendency to ruminate. Surprisingly, when we re-administered the RRS at the start of an experimental session, significant score changes occurred, resulting in participants shifting between the two groups. Methods To address this, we modified our recruitment process, aiming to reduce careless responses, including an online RRS assessment a week before the lab appointment. We analyzed the different samples prior to and after changing the recruitment procedure, as well as the total sample regarding the psychometric properties of the RRS. We also explored various indices to identify and predict score changes due to careless responding; however, only a subgroup of participants was successfully identified. Results Our findings suggest that Mahalanobis distances are effective for identifying substantial score changes, with baseline state rumination emerging as a marginally significant predictor. Discussion We discuss the importance of conducting manipulation checks and offer practical implications for research involving psychometrically validated trait questionnaires.